Environmental Land Use Planning and Socio-environmental Conflicts in the Tigre Delta, Argentina - Astelarra, Sofía (2025)
This article examines the socio-environmental conflicts that emerged during the development and implementation of Argentina’s first environmental land-use planning (ELUP) policy in wetlands, specifically the Comprehensive Management Plan for the Delta in the municipality of Tigre, Buenos Aires Province. Drawing on the theoretical frameworks of political ecology and territorial planning and based on interviews with key stakeholders and field observations, the article argues that the elaboration of plan was the result from productivities, that is, from the conflicts between the community and civil society organizations on one side, and real estate developers promoting luxury gated communities on the other, amid the absence of environmental regulation. The plan’s implementation generated new conflicts and processes of re-signification of the delta, the islands, and the river, driven by increased citizen participation in decision-making processes.